Implementation of MRP systems as a tool for improving inventory management efficiency in FMCG companies - Hasenko, Yuliia (Актуальні питання економічних наук, 2025)
The relevance of the research is determined by the growing need of FMCG companies to increase the efficiency of inventory management under conditions of market turbulence, disrupted supply chains, and intensified competition. Traditional planning methods often fail to ensure a rapid response to demand fluctuations, resulting in excessive inventories, reduced turnover, and financial losses. In this context, the implementation of Material Requirements Planning (MRP) systems becomes a crucial tool for optimizing material flows and enhancing the flexibility of production and distribution processes. The purpose of this article is to substantiate the effectiveness of implementing the MRP system as a tool for enhancing inventory management performance in FMCG companies, with a focus on practical results related to optimizing procurement and production planning, reducing excessive inventories, and improving operational flexibility and business resilience. The research methodology is based on a combination of systematic, analytical, and comparative approaches. Methods of economic modeling, logistics process efficiency analysis, and case-study techniques were employed to evaluate the practical outcomes of MRP implementation in national and international FMCG companies, along with statistical generalization methods to identify patterns of inventory reduction and cost optimization. Research results revealed that integrated MRP solutions lead to a 30–45% reduction in excessive inventories, a 20–25% decrease in operating costs, and up to a 50% increase in resource turnover. It has been proven that integrating MRP with Big Data analytics, IoT technologies, and demand forecasting systems enhances the adaptability and resilience of supply chains to external risks. Conclusions. Confirm that MRP functions as a practical analytical framework for building data-driven inventory management systems that combine precision, adaptability, and operational sustainability. Prospects for further research include developing quantitative models to evaluate the economic impact of digitalized material planning, forming recommendations for harmonizing Ukrainian practices with international standards such as APICS CPIM and the European Logistics Association, and expanding MRP applications in the context of post-war recovery and the global integration of Ukrainian FMCG companies.